Longitudinal assessment of late-onset neurologic conditions in survivors of childhood central nervous system tumors: a Childhood Cancer Survivor Study report. Issue 1 (22nd August 2017) - Wells, Elizabeth M; Ullrich, Nicole J; Seidel, Kristy; Leisenring, Wendy; Sklar, Charles A; Armstrong, Gregory T; Diller, Lisa; King, Allison; Krull, Kevin R; Neglia, Joseph P; Stovall, Marilyn; Whelan, Kimberly; et al.
Abstract: Background: Survivors of childhood central nervous system (CNS) tumors experience high rates of treatment-related neurologic sequelae. Whether survivors continue to be at increased risk for new events as they age is unknown. Methods: Adverse neurologic health conditions in 5-year survivors of CNS tumors from the Childhood Cancer Survivor Study ( n = 1876) were evaluated longitudinally at a median 23.0 years from diagnosis (range, 5.1–38.9), median age at last evaluation 30.3 years (range, 6.1–56.4). Multivariable regression estimated hazard ratios (HRs) and 95% CIs. Results: From 5 to 30 years post diagnosis, cumulative incidence increased for seizures from 27% to 41%, motor impairment 21% to 35%, and hearing loss 9% to 23%. Risks were elevated compared with siblings (eg, seizures HR: 12.7; 95% CI: 9.6–16.7; motor impairment HR: 7.6; 95% CI: 5.8–9.9; hearing loss HR: 18.4; 95% CI: 13.1–25.9). Regional brain doses of radiation therapy were associated with development of new deficits (eg, frontal ≥50 Gy and motor impairment HR: 2.0; 95% CI: 1.2–3.4). Increased risk for motor impairment was also associated with tumor recurrence (HR: 2.6; 95% CI: 1.8–3.8), development of a meningioma (HR: 2.3; 95% CI: 0.9–5.4), and stroke (HR: 14.9; 95% CI: 10.4–21.4). Seizure risk was doubled by recurrence (HR: 2.3; 95% CI: 1.6–3.2), meningioma (HR: 2.6; 95% CI: 1.1–6.5), and stroke (HR: 2.0; 95% CI: 1.1–3.4). Conclusions: CNS tumor survivors remain at risk for new-onset adverse neurologic events across their lifespans at a rate greater than siblings. Cranial radiation, stroke, tumor recurrence, and development of meningioma were independently associated with late-onset adverse neurologic sequelae.